Legal entity of the Catholic Church as a participant in Land and Mortgage Register proceedings in Polish law – selected issues - Włodzimierz Broński; Piotr Sławicki (Studia z Prawa Wyznaniowego)
This article evaluates the legal norms related to real estate trading by legal entities of the Catholic Church in the context of land and mortgage register proceedings. First, the issue of the legal entity of the relevant church legal entities is presented. Next, the principles of the representation of church legal entities by the competent authorities is analysed. This is important both for the capacity to undertake a substantive legal action, the subject of which is real estate, and for examining the effectiveness of procedural steps taken in the course of land and mortgage register proceedings. The last part is devoted to real estate trading with the participation of church legal entities in the context of the principles resulting from the regulations of land and mortgage register proceedings. The research leads to the conclusion that for land and mortgage register proceedings, it is of fundamental importance to assess the effectiveness of a legal act in the context of the specific requirements of canon law, examples of which are Canons 1281 § 1 of the Code of Canon Law with regard to acts exceeding the limits and manner of ordinary management, and Canons 1292 § 1–2 of this Code making the validity of alienation dependent on the consent or authorisation of the competent entity. The absence of the consent or authorisation required by the provisions of canon law should lead to dismissal of the application for entry, which can possibly be remedied by a subsequent confirmation of the legal act performed by applying the instruments of civil law, as exemplified by Articles 39 and 63 of the Civil Code. In addition, the implementation of the principle of the autonomy of the Catholic Church is expressed in leaving to the church authority regulation of the appointment of the competent bodies of church legal persons; the land and mortgage register court cannot question the effectiveness of the appointment of these bodies, the assessment of which is left to the Catholic Church and its organisational units.